AN ANALYSIS OF STUDENTS’ ABILITY IN WRITING RECOUNT TEXT IN SMA JOSEPH KHATULISTIWA - Artalina Silitonga; Henry Elisa; Yokie Prasetya Dharma (INOVISH JOURNAL, 2022)
Abstract: The research was carried out due to students having low ability in writing. The research aims are to describe students' ability in writing recount text and students' errors in using language features in writing recount text. This research used qualitative research. Data were collected using documentation techniques. Data collection tools are documents. The average of students' ability in content aspect is 35%, organization aspect is 23%, vocabulary aspect is 17%, grammar aspect is 20% and mechanic's aspect is 5%. The number of students' errors in writing recount text is 79 items. The omission error was 35 (44%), addition error was 13 (17%), misformation was 23 (29%) and misordering was 8 (10%). It was concluded the most mastered ability of students in writing recount text was content aspect and the lowest was in mechanic's aspect. The type of students' errors using language features was omission and the lowest in misordering.